Migration and Accumulation of Heavy Metals in Soils and Crops around Coal Gangue Hill - Xiaoyan Xu, Lianglun Sun, Guoquan Zhang, Lili Xie, Zhina Guo, Ying Hu, Yan Gao (Forest Chemicals Review)
Concerns about soil heavy metal contamination have continued to rise in recent years, particularly concerning the surrounding soil heavy metal contamination caused by the prolonged stockpiling of coal gangue. In this study, we collected the surrounding soil and corn from a coal gangue hill in Qufu, Shandong Province, detected the content and occurrence forms of soil heavy metals, analyzed the correlation between coal gangue and soil heavy metals, and evaluated the impact of heavy metal pollution on environmental quality of the site. The results showed that Hg and Cd were major pollutants in coal gangue hill, which had reached serious pollution levels, and the content of the other was all lower than the risk control values in agricultural lands. With the distance from the coal gangue hill center from near to far (0-150 meters), the occurrence modes of soil heavy metals gradually increased to stable, and the potential risk decreased accordingly. The absorption and storage capacity of Pb in corn kernels was the strongest, which led to the content exceeding the standard by about 85.7 times. The study provided a reliable theoretical basis for the rational deposition of coal gangue and ecological environmental protection in the region.